Cardiopulmonary coupling-calculated sleep stability and nocturnal heart rate kinetics as a potential indicator for cardiovascular health: a relationship with blood pressure dipping - Hilmisson, Hugi; Thomas, Robert Joseph; Magnusdottir, Solveig (Frontiers in Sleep, 2024)
High blood pressure (HBP) is an independent, modifiable driver of cardiovascular (CV) morbidity and mortality. Nocturnal hypertension and non-dipping of blood-pressure (NdBP) may be early markers of HBP. Similarly, to paUents with NdBP, individuals with non-dipping of heart rate (NdHR) during sleep have an increased risk of CV-disease, CV-events and CV-related mortality. The aim of this analysis was to evaluate if cardiopulmonary coupling (CPC)-analysis derived sleep states (stable/unstable non-rapid eye movement [NREM] sleep) and concomitant HR changes can provide informaUon about nocturnal BP.Plethysmogram (PLETH)-signals from the HeartBEAT-study (NCT01086800) were analyzed for CPC-sleep-states. Included in the analysis are sleep recordings from parUcipants (n=302) with acceptable PLETH-signal quality at baseline (n=302) and follow-up (n=267), all having confirmed CV-disease or CV-disease risk factors. The parUcipants had a high prevalence of obstrucUve sleep apnea (OSA), 98.4% with moderate-OSA (apnea hypopnea index, AHI ³15) and 29.6% severe-OSA (AH³30). IA "Heart-rate-module" was created to evaluate uUlity to idenUfy paUents more likely to have BP-dipping during sleep. PaUents who did not decrease ³10% in BP from wake to sleep were defined as NdBP and NdHR if HR during stable-NREM-sleep was higher than during unstable-NREM-sleep.The most significant difference in minimum HR (HRmin) was observed when comparing BP-dippers (56 ± 4 BPM) and non-BP-dippers (59 ± 4 BPM ) (p<0.0001) during diastolic bloodpressure in stable NREM-sleep. Higher HRmin were associated with an increased likelihood of being a non-dipper, with the strongest relaUonship with diastolic-BP and stable-NREM sleep.Every increase of 1-BPM during stable-NREM sleep was associated with ~4.4% increase in probability of being non-dipper (p=0.001). Non-dipping HR subjects have higher mean, sleep and wake-BP than HR-dippers. When CPAP-therapy is efficacious, and dipping-paXern is achieved -physical, and mental health is improved.HR-analyUcs in relaUon to the sleep period and CPC-spectrogram-esUmated sleep-states can provide novel and potenUally clinically useful informaUon on autonomic health. HR-dipping (or not) may be a useful screener of BP-dipping/non-dipping, to idenUfy individuals who may benefit from formal assessment of 24-hour-ambulatory BP. Such a stepped approach may enable a more pracUcal and applicable approach to diagnosing HBP.